Advancing Tourism Support in Emerging Destinations: Quality of Life as a Mediator in Emotional Solidarity Dynamics - Muhammad Rachmat; Christy Natalia Rondonuwu; Moh. Amin Rosidi (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This study examines the influence of emotional solidarity and quality of life on residents’ support for tourism development in Ternate, Indonesia, an emerging destination with tourism infrastructure constraints, utilizing Social Exchange Theory (SET) as a theoretical framework. Data from 416 residents, collected through a carefully crafted survey, were analyzed using structural equation modeling to assess the interplay among Welcoming Nature, Emotional Closeness, Sympathetic Understanding, Quality of Life, and Support for Tourism. Findings reveal that Welcoming Nature and Emotional Closeness significantly enhance Quality of Life and tourism support, with Quality of Life partially mediating these effects. Sympathetic Understanding, however, has minimal impact due to limited resident-tourist interactions. By advancing emotional solidarity and Social Exchange Theory, this study highlights the critical role of affective factors in emerging tourism contexts. The cross-sectional design limits insights into temporal trends, necessitating longitudinal research, while comparative studies are essential to test generalizability.  The study suggest that improving infrastructure and promoting community-based festivals can foster sustainable tourism by enhancing resident-tourist interactions and quality of life. Policymakers and tourism planners should prioritize community engagement to ensure equitable tourism development. This research offers a novel application of emotional solidarity and SET in an underexplored emerging destination, emphasizing the mediating role of quality of life and the limited influence of Sympathetic Understanding in contexts with constrained resident-tourist interactions